A double dipole kicker for off and on-axis injection into ALBA-II. Issue 1 (1st January 2023) - Benedetti, G; Carlà, M; Pont, M
Abstract: Injection into the ALBA-II storage ring will be performed off-axis in a 4 meters straight section with a single multipole kicker. We present a novel topology for the coils of the injection kicker, named double dipole kicker (DDK). The resulting magnetic field is the superposition of two opposite dipoles, generated by four inner and four outer conductor rods. When the eight rods are powered, the dipole term cancels and the remaining multipole field is used for off-axis injection. Alternatively, when the four inner rods are switched off, an almost pure dipole is produced, that is useful for on-axis injection during the commissioning. A prototype of DDK is presently under design to be installed and tested in the existing ALBA storage ring. The positioning of the rods is calculated in order to maximize the kick efficiency in mrad/kA and minimise the disturbance to the orbit and the emittance of the stored beam. A metallic coating with optimised thickness along the inner ceramic vacuum chamber should provide compensation for the eddy currents induced field in order to minimize the disturbance to the stored beam while ensuring sufficiently low heat dissipation by the beam image currents.